2021
DOI: 10.1097/scs.0000000000007488
|View full text |Cite
|
Sign up to set email alerts
|

External Nose Anthropometry of Healthy Turkish Young Adults

Abstract: Although many studies in the literature examine distances and angles about the nose, there are no clear standard values for different races and ethnic groups. The aim of this study is to determine the anthropometric measurement standards related to the external nose in Turkish young adults between the ages of 18 and 25. The subjects participating in this study were 100 female and 100 male volunteers. Six landmarks (nasion, subnasale, pronasale, alar, subalar and maxillofrontale) on the nose were chosen, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 47 publications
4
17
1
Order By: Relevance
“…20 Morphological nose width (al-al) values of the Turkish population vary between 41.07 ± 2.92 and 35.24 ± 2.70 mm in men and between 36.53 ± 2.65 and 31.59 ± 2.50 mm in women. 16,18 The morphological nose width measurements obtained in this study were within the range of the Turkish population (men, 37.25 ± 2.8 mm; women, 35.39 ± 3.42 mm). This value was reported as 35.50 ± 0.37 mm and 38.90 ± 9.3 mm in male rhinoplasty patients in 2 different studies.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…20 Morphological nose width (al-al) values of the Turkish population vary between 41.07 ± 2.92 and 35.24 ± 2.70 mm in men and between 36.53 ± 2.65 and 31.59 ± 2.50 mm in women. 16,18 The morphological nose width measurements obtained in this study were within the range of the Turkish population (men, 37.25 ± 2.8 mm; women, 35.39 ± 3.42 mm). This value was reported as 35.50 ± 0.37 mm and 38.90 ± 9.3 mm in male rhinoplasty patients in 2 different studies.…”
Section: Discussionsupporting
confidence: 63%
“…The mean nasofrontal angle in the Turkish population varies between 123.85°±13.23° and 146.03°±8.19° in men and between 133.16°±8.88° and 148.61°±6.66° in women 18,31–33. The mean nasolabial angle varies between 90.32°±11.8° and 102.92°±10.91° in men and between 95.07°±10.42° and 104.4°±12.7° in women 2,13,18,31–33.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…29,30 Considering the clinical differences between the genders, differences in anthropometric measurements between the genders can also be expected. 31 In our study, orbital measurements were found to be significantly higher in males, but there was no significant difference in females. All linear soft-tissue orbital dimensions were found significantly larger in males than in females in a study examining anthropometric differences between the genders in healthy individuals.…”
Section: Discussioncontrasting
confidence: 45%